2014
DOI: 10.1111/ane.12311
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of refractory epilepsy patients rejected from epilepsy surgery

Abstract: A considerable minority of patients with refractory epilepsy who were rejected or chose not to undergo epilepsy surgery may improve over time and even become seizure-free following adjustment of anti-epileptic drugs with or without concomitant VNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…We also assessed seizure outcome in those patients who did not undergo surgery, and seizure freedom rate was similar in those who were not eligible and those who denied resection or necessary further VEMs (11 to 15%). These figures are in line with previous studies from Canada and Israel on non-operated patients reporting seizure freedom rates of 8% 1 year after presurgical evaluation 3 and of 17% after 4 years 21. These figures indicate that patients who decline VEM at different phases of the diagnostic evaluation process or who decide against eventual resective surgery must be counseled on unfavorable seizure outcome.…”
supporting
confidence: 90%
“…We also assessed seizure outcome in those patients who did not undergo surgery, and seizure freedom rate was similar in those who were not eligible and those who denied resection or necessary further VEMs (11 to 15%). These figures are in line with previous studies from Canada and Israel on non-operated patients reporting seizure freedom rates of 8% 1 year after presurgical evaluation 3 and of 17% after 4 years 21. These figures indicate that patients who decline VEM at different phases of the diagnostic evaluation process or who decide against eventual resective surgery must be counseled on unfavorable seizure outcome.…”
supporting
confidence: 90%
“…Whilst the benefits of MKD on seizure frequency described above may support its use as an intervention in refractory epilepsy, it has previously been observed that as many as 17% of patients with refractory epilepsy achieve seizure freedom by continuing their usual medical therapy [32]. In addition, we note that the proportion experiencing worsening of seizure frequency was relatively high in this study at 30%, particularly when compared to initiation of new AEDs [33].…”
Section: Discussionmentioning
confidence: 46%
“…Finally, the volumes ranged from 0.7 to 4.5 cm 3 (volumes: 6.2 to 6.9 cm 3 , 5.5 to 6.9 cm 3 , and 7.8 to 12.3 cm 3 ; respective seizure‐free rates: 86%, 50%, and 20%). In addition, other factors some of which are yet to be characterized may have an impact on success including differences among patients in epileptic networks . These differences may also account for the observed heterogeneity in the type and frequency of AEs reported by patients in each of the studies.…”
Section: Discussionmentioning
confidence: 99%